Evaluating the exchange rate and commodity price nexus in Malaysia: Evidence from the threshold cointegration approach - Shamaila Butt; Suresh Ramakrishnan; Nanthakumar Loganathan; Muhammad Ali Chohan (Financial Innovation, 2020)
This paper examines the long- and short-run dynamics of asymmetric adjustment between the nominal exchange rate and commodity prices, namely oil, palm oil, rubber, and natural gas prices, in Malaysia using monthly data from January 1994 to December 2017. The relationship between exchange rate and each commodity price is examined in terms of Engle-Granger and threshold cointegrations. The estimated results provide evidence of long-run threshold cointegration and show that the adjustments towards the long-run equilibrium position are asymmetric in the short run. Furthermore, this study finds evidence of a unidirectional causal relationship running from the nominal exchange rate to oil price in the long and short run using a spectral frequency domain causality application. There is also empirical evidence of bidirectional causality between the nominal exchange rate and palm oil price, rubber price, and natural gas price in the long and short run. Overall, the findings have significant implications for the current debate on the future of primary commodities in Malaysia.
Keywords: 650; Commodity prices; Exchange rate; Threshold cointegration